KONSTRUKSI REALITAS KEHIDUPAN SOSIAL KOMUNIKASI PADA ANAK USIA DINI PECANDU GAME ONLINE - Weldy Bilhuda (2022)
This study aims to determine what the patterns of social life communication look like for kids addicted to online games in real life, to determine interactions pattern and communication for kids addicted to online games. The researcher is conducting this research by a qualitative approach, such as using descriptive qualitative along with the phenomenological method. Data collection techniques that using for this research are observations, documentation, and free guide interviews along with three interviewees. For Analysis technique is using phenomenological data analysis by Moustakas, which consists of six steps. there are the first step, horizontal step, cluster of meaning step, textural of description development step, structural of description step, synthesis textural and structural of description. The result of this research is to present the transformation of reality constructions of social communication for kids who are addicted to online games such as, not being heedful of their surroundings, being more emotional, forgetting their time, and saying some harsh words. Besides, interactions pattern and communication for kids addicted to online games becomes disturbed and changed because the focus of children is now only on playing gadgets or playing online games, so that when socializing and interacting and communicating will be more closed and it will be difficult for children to communicate. adapt to the environment in which the child lives. In addition, shaping the child's personality becomes more individualistic.